2019
DOI: 10.1029/2018gl080761
|View full text |Cite
|
Sign up to set email alerts
|

Carbonate Dissolution Enhanced by Ocean Stagnation and Respiration at the Onset of the Paleocene‐Eocene Thermal Maximum

Abstract: The Paleocene‐Eocene Thermal Maximum was a transient, carbon‐induced global warming event, considered the closest analog to ongoing climate change. Impacts of a decrease in deepwater formation during the onset of the Paleocene‐Eocene Thermal Maximum suggested by proxy data on the carbon cycle are not yet fully understood. Using an Earth System Model, we find that changes in overturning circulation are key to reproduce the deoxygenation and carbonate dissolution record. Weakening of the Southern Ocean deepwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…6b), therefore, supports a rapid carbon emission rate towards a 5 kyr perturbation period and also suggests more stagnant deep waters during the PETM onset with slower ventilation rates than the present-day ventilation rates. Our inference is in agreement with previous studies 44,45 suggesting an overall decline in deep ocean ventilation rates during the PETM onset, possibly linked with the reorganization of deep ocean circulation patterns 10,46,47 . There remain important aspects of the observed PETM δ 13 C-DIC excursion that are not captured by our simulation, including much delayed and reduced declines in benthic δ 13 C, slight 13 C-enrichments in benthic δ 13 C prior to declines, and different magnitudes of benthic δ 13 C declines between the two ODP sites (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…6b), therefore, supports a rapid carbon emission rate towards a 5 kyr perturbation period and also suggests more stagnant deep waters during the PETM onset with slower ventilation rates than the present-day ventilation rates. Our inference is in agreement with previous studies 44,45 suggesting an overall decline in deep ocean ventilation rates during the PETM onset, possibly linked with the reorganization of deep ocean circulation patterns 10,46,47 . There remain important aspects of the observed PETM δ 13 C-DIC excursion that are not captured by our simulation, including much delayed and reduced declines in benthic δ 13 C, slight 13 C-enrichments in benthic δ 13 C prior to declines, and different magnitudes of benthic δ 13 C declines between the two ODP sites (Fig.…”
Section: Resultssupporting
confidence: 94%
“…These disparities imply that concomitant transient changes in ocean circulation, marine biology, land-derived carbon inputs, and marine sedimentary dissolutions of CaCO 3 might have been as important as the geochemical effects for the early PETM δ 13 C excursion (e.g., refs. 10,11,21,44 ). In fact, Kirtland Turner and Ridgwell 11 showed that the CO 2 -climate feedbacks during the PETM onset can delay the time that it takes for the surface δ 13 C-DIC minimum to propagate to the deep ocean δ 13 C-DIC minimum by up to 40%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[57]) and according to the scale considered [58]. Additionally, such variations might be difficult to constrain in the geological record without modelling—so far only available for a limited number of time-slices, such as at the Palaeocene–Eocene Thermal Maximum [59,60].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in O 2 supply (“ventilation”) by upper-ocean circulation cannot be ruled out. However, rapid warming intervals are typically associated with reduced rates of ventilation ( 42 ), which would tend to work against the observed PETM oxygenation, exacerbating the need for lower tropical productivity. With regard to nutrient concentration, there have been suggestions of a global increase in nutrient reservoir during the PETM ( 43 ); this alone would increase nutrient supply to tropical surface waters, the opposite of what is needed to explain the Site 865 data and the ODZ contraction.…”
Section: Mechanisms Of Upper-ocean Oxygenation In a Warming Climatementioning
confidence: 99%